Enriched Environment Exposure Enhances Social Interactions and Oxytocin Responsiveness in Male Long-Evans Rats - Neal, Steven; Kent, Molly; Bardi, Massimo; Lambert, Kelly G. (Frontiers in Behavioral Neuroscience, 2018)
In the current study, male Long-Evans rats were randomly assigned to an isolate (ISO), social control (SC) or social enriched (SE) group (n=8 per group). The SC and SE conditions were group housed with the SE group exposed to physical enrichment stimuli that were natural as opposed to manufactured (e.g., hollowed out log instead of plastic hiding place). On three occasions during their 40-day enriched environment exposure, night/dark phase videos were obtained for one hour during the early part of the dark phase. During this time, the SE animals exhibited significantly more social grooming with no differences between the SE and SC in the frequency of play or self-grooming bouts. Subsequently, all animals were assessed in social interaction and problem-solving escape tasks during the last week of the enriched environment exposure. SE rats exhibited increased digging bouts toward the restrained conspecific in the social interaction task (behavior indicative of attention directed toward the distressed animal) whereas the other groups exhibited more escape responses (behavior indicative of attention directed away from the distressed animal). In the problem-solving task, SE animals exhibited a decreased latency to cross the barrier to escape from the predator odor (i.e., cat urine and fur). Neural analyses indicated increased oxytocin-immunoreactive tissue in the SE supraoptic and paraventricular nuclei of the hypothalamus compared to the other groups. Interestingly, blood samples indicated lower peripheral corticosterone and higher oxytocin levels in the ISO animals when compared to the EC and ES animals, an effect retrospectively attributed to separation anxiety in the ES and EC animals in preparation for histology procedures. When the behavioral, neural and endocrine data were visualized as a multifaceted dataset via a multidimensional scaling analysis, however, an association between social enrichment and higher oxytocin involvement was observed in the ES animals, as well as heightened stress responsivity in the ISO and SC groups. In sum, the natural-enriched environment utilized in the current study facilitated the expression of physical and social environmental interactions that were accompanied by enhanced oxytocin-based neural functions and altered behavioral responses.